FEASIBILITY AND EFFICIENCY OF SWEET CORN FARMING IN JANTI VILLAGE, PAPAR DISTRICT, KEDIRI DISTRICT - Yulianto, Mohammad Bagus; Fatmawati, Erlin Widya; Maharani, Navita (AGROLAND The Agricultural Sciences Journal (e-Journal), 2025)
Corn farming plays a crucial role in supporting the agricultural economy of rural communities, particularly in regions with fertile land and favorable climate conditions. Farmers need to conduct evaluations regarding the use of more efficient production factors in order to remain sustainable. The purpose of this study was to determine the feasibility and price efficiency of corn farming in Janti Village, Papar District, Kediri Regency. The location of the research conducted in Janti Village, Papar District, Kediri Regency. This research was conducted in November 2022 – January 2023. The method in this study is calculated costs, receipts, profits, Break-Even Point (BEP), and the R/C Ratio. To evaluate price efficiency, the research conducted allocative efficiency calculations, comparing actual input use (seeds and pesticides) to efficient input levels. Observation by direct observation of corn farming in Janti Village, Papar District, Kediri Regency. The number of samples for the study was calculated usin the Slovin formula, Therefore there are total of 66 samples of corn farmers were obtained and determined using a simple random sampling method. The analysis method used for the first problem is by using the calculation of cost, receipt, profit, BEP and R/C Ratio while to answer the second problem using price efficiency calculations. The results of the feasibility analysis show that the average total profit for corn farmers in one harvest season is IDR 31,235,000/ha. So that the value of BEP Production Prices is 1.855 and Production Volume BEP is 6.730. The R/C value is 2.20 with the interpretation that corn farming in Janti Village, Papar District, Kediri Regency is profitable and feasible to cultivate. The results of the allocative efficiency analysis of corn farming show that the use of 25 kg/ha seed in one growing season is not efficient, because the efficient average use of seed is 26.8 kg/ha. While the use of pesticides 15 liters/ha in one growing season is not efficient, because the average efficient use of pesticides is 17.6 liters/ha.